Decolonizing Feminist Legal Methods: A Study of the Criminalization of Women and Imprisonment for Drug Offenses - Ferreira, Letícia Cardoso [UNESP]; Braga, Ana Gabriela Mendes [UNESP] (Sistema de Bibliotecas PUCP, 2023)
Feminists take a variety of different approaches to discussions of the law, and many researchers have focused on studying the possibility of employing feminist legal methods of “doing” and “knowing” in law. Feminist authors discuss the possibility of applying feminist methods to question truth claims in law and challenge the power relations the law creates and recreates based on markers such as gender, race, and class. We have organized our work around three components of a method developed by Katharine Bartlett —the woman question, feminist practical reasoning and consciousness-raising—to analyze the knowledge produced regarding the imprisonment of women for drug offenses in Brazil in the 21st century. We consider how feminist methods may be applied in this and other contexts which involve a great deal of marginalization. Drawing on Ochy Curiel’s interpretation of the concept of the coloniality of knowledge, we ask: How can we decolonize feminist methods in order to adapt them to the needs and realities of the Global South? We focus on the idea of translation, advocated for by a number of Latin American and North American authors whose work touches on themes of centrality (North) and marginality (South), as a method of producing “connected epistemologies” which encourage alliances and challenge reductionist interpretations of feminist theories. Our aim is to contribute to a horizontal dialogue between the Global North and South in feminist studies without disregarding the uniqueness of the realities of our research subjects.
Decolonizando los métodos jurídicos feministas en una investigación acerca del fenómeno de la narcocriminalización delasmujeres
Keywords: Brazil; criminal woman; decolonial feminism; Feminist methodologies; translation